Nutrition Education for Refugees: Successful Strategies and Barriers - Jessica Smith; Habiba Nur; Martha Archuleta; Mateja R. Savoie-Roskos; Celina Wille; Casey Coombs; Heidi J. Wengreen (Journal of Human Sciences and Extension)
Nutrition education can improve nutrition and health for refugees. Extension program directors providing nutrition education to refugees were surveyed regarding successful program techniques, program challenges, and both the barriers refugees face and the strengths they possess concerning healthy eating. Researchers used grounded theory to explore the qualitative data. Handson, skill-based learning emerged as a main theme of successful programs. Language and cultural issues emerged as main program challenges. It is recommended that future refugee nutrition education programs provide culturally sensitive opportunities for skill-based learning.